Hydrothermal syntheses and characterization of a new metal–organic framework of gadolinium(III) with 2, 4, 6-tris(3, 5-dicarboxylphenyl-amino)-1, 3, 5-triazine. (27th July 2017) - Liu, Kang; Sun, Yuexin; Hu, Hanbin; Wang, Lei
Graphical abstract: We synthesize and characterize a new microporous gadolinium metal–organic framework Gd(H3 TDPAT)·H2 O which shows a unusual nia topology. Abstract: A new microporous gadolinium metal–organic framework formulated as Gd(H3 TDPAT)·H2 O (1 ) (H6 TDPAT = 2, 4, 6-tris(3, 5-dicarboxylphenyl-amino)-1, 3, 5-triazine) was hydrothermally synthesized. The compound was fully characterized by elemental analysis, IR spectroscopy, thermogravimetric analysis, power X-ray diffraction and single-crystal X-ray diffraction. It crystallizes in the hexagonal system, space group P 31 c with cell parameters a = 12.8501(18) nm, c = 15.709(3) nm and γ = 120°. The compound was polymeric with Gd III atoms linked by nine oxygen atoms from six carboxylate groups of H3 TDPAT 3− ligands and structurally characterized as a unusual nia topology with (6, 6) nodes (Schläfli symbol is 4 12 ·6 3 4 9 ·6 6 ). Moreover, the adsorption behavior and magnetic property have been studied and discussed.